Hydrogen Tungsten Bronze‐Supported Platinum as Electrocatalyst for Methanol Oxidation. Issue 2 (16th January 2013) - Li, X. P.; Xiang, X. D.; Yang, H. Y.; Wang, X. J.; Tan, C. L.; Li, W. S.
Abstract Hydrogen tungsten bronze (HxWO3)‐supported platinum was prepared by electrodeposition and used as an electrocatalyst for methanol oxidation. The prepared electrocatalyst was characterized by Raman spectrum, X‐ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), cyclic voltammetry (CV), and chronoamperometry (CA). It is found that the support, HxWO3, not only reduces the platinum particle size and thus reduces the platinum loading, but also provides platinum with the anti‐poison ability to carbon monoxide and thus improves the activity of platinum toward methanol oxidation.